Design de embalagem para transporte de garrafas, da adega para o consumidor final - Zaniboni, Fillipy Redivo (2013)
This work aims to be the first step to launching a new package for wine transport. It is a package that attaches to another of the same model, ensuring the protection of each bottle individually. Were analyzed technical aspects related to the raw material (paper card) as the market factors. The research confirmed the importance of security through transportation. Is relevant to note that all stages of the project were designed based in the mobility and protection of the product transportation.